Wood is good : current trends and future prospects in wood utilization - Pandey, Krishna K.; Ramakantha, V.; Chauhan, Shakti S.; Kumar, A. N. Arun (Springer, 2017)
This book is a compilation of selected papers presented in the International Conference on the theme Wood is Good: Current Trends and Future Prospects in Wood. The contents of the book deal with recent innovations, trends and challenges in wood science and are grouped in five distinct sections. They cover a wide range of topics like wood variability, processing and utilization, wood protection, wood-based composites, wood energy and the role of wood in mitigating climate change. With the ever increasing human population and growing demand for wood, this book offers valuable insights for better understanding and efficient utilization of this wonderful gift of nature. This book will be useful to researchers, professionals, and policy makers involved in forestry and wood related areas.
Includes author index.
Keywords: Wood.; Timber.; elektronické knihy; electronic books